PERLINDUNGAN KONSUMEN ANAK DI BAWAH UMUR YANG MENGKONSUMSI TAYANGAN ELSAGATE - Reyza Julianda Mahabati; Ariawan Gunadi (Jurnal Hukum Adigama, 2022)
in this digital era, information and communication are increasingly developing and making it easier for its users to find or access some information circulating on the internet. The ease of searching for various information on the internet makes internet users not only an adult but also minors who can use the internet proficiently. The internet can be used for various groups of age because apart from being a medium to find a piece of information, it can also be used as an entertainment medium. One of the media that is often used by internet users as a medium of information and entertainment is Youtube. The purpose of this study is to explain in depth the Elsagate impression consumed by minors. These minors have a very high curiosity and these minors have minor properties without filtration. These things can be very risky because minors will capture and remember what they see and feel and they will apply it to their behavior.